Remote monitoring of chronic noncommunicable diseases: potential in the COVID-19 pandemic - O. S. Kobyakova; I. A. Deev; D. S. Tyufilin; G. O. Alexandrov; E. S. Kulikov (Бюллетень сибирской медицины)
Aim. To review the current progress in the use of remote health monitoring (RHM) technologies for chronic noncommunicable diseases (CNCD).To search for data, we used Web of Science, Scopus, Russian Science Citation Index, Academic Search Complete (EBSCO), Cochrain, and PubMed databases. The date range was 5–10 years. The importance of development of RHM technologies and their further study was shown to confirm the evidence of effect of certain RHM systems.New approaches to the integration of the medical community into the international telemedicine strategy are considered. It was established that RHM can potentially decrease treatment costs and reduce the burden on medical organizations. The review analyzes the experience in using RHM in patients with cardiovascular diseases, as well as respiratory and endocrine disorders. The review also summarizes and systematizes the findings of studies on assessing the effectiveness of RHM technologies in clinical practice, including their use in the COVID-19 pandemic.It is noted that despite high interest of the scientific community in the study of RHM technologies, unambiguous results demonstrating the effectiveness of such developments in clinical practice have not been presented.